Integrating semiotic resources in the production of mathematical videos: analysis of a video produced by students in the final years of elementary school (Revista BOEM, 2024)
The article reports on an experience of mathematical video production by students in the final years of Elementary School, aimed at analyzing, in the produced video, how students used and integrated semiotic resources to communicate mathematical knowledge.The methodology employed was qualitative in nature. The analysis was conducted using the Systemic Functional Theory -Multimodal Discourse Analysis, which allows not only to investigate the relationship between visual, verbal, and auditory elements present in this type of media but also to understand how these elements relate and contribute to the overall meaning of the video. This analysis enables us to identify the communication strategies used by students, as well as to understand the effect of these resources on the comprehension of mathematical concepts by viewers. In the analysis of the produced video, the combination of semiotic resources, such as sounds, images, mathematical symbols, gestures, colors, written and oral language, reveals a multimodal approach that seeks to communicate mathematical concepts in a captivating and meaningful way.
Keywords: video production; mathematical knowledge; multimodality; semiotic resources